Mechanism of ferroptosis and its role in kidney diseases - Gong Mei-ling; Li Jun-hua (Linchuang shenzangbing zazhi)
Regulatory cell death（RCD） is essential for the development of organisms and the maintenance of homeostasis.Previously apoptosis was deemed as a sole form of RCD.However, recent studies have demonstrated that RCD could proceed through apoptosis or one of several non-apoptotic cell death pathways, including recently described ferroptosis and pyroptosis.Ferroptosis is a new form of cell death in nerve cell injury.Triggered by an inactivation of glutathione（GSH） dependent antioxidant defense system, it results in an accumulation of lipid peroxidation products and reactive oxygen species（ROS）.The latest evidence has indicated that ferroptosis was correlated with acute kidney injury（AKI）,chronic kidney disease（CKD）,polycystic kidney disease and renal cell carcinoma（RCC）,etc.And the development of related kidney disease could be intervened by activating or inhibiting ferroptosis.This review examined the discovery, characteristics and mechanism of ferroptosis and its relationship with kidney diseases, summarized the major regulatory mechanisms of ferroptosis and explained the relationship between ferroptosis and kidney disease to provide a new potential therapeutic target for kidney disease.